The Universe as a Great Human Being: Eco-Cosmology in Rasāʾil Ikhwān al-Ṣafāʾ = ālʿālm āʾnsān kbīr: ʿlm ālkūn ālbīīʾī fī «rsāīʾl» āʾḫūān ālṣfā - Darraz, Muhammad Abdullah (Journal of Islamic ethics, 2025)
The ecological crisis represents a significant challenge to our intellectual and spiritual understanding, reflecting a crisis in our comprehension of the relationship between humanity and the natural world. The reality of nature has been constrained by the limitations of human knowledge, which perceives nature as simply a physical entity devoid of its metaphysical and spiritual dimensions. Consequently, nature is regarded as a mere aggregation of inanimate objects that humans can treat indifferently. This research project aims to explore the concept of the universe as a great human being (al-ʿālam insān kabīr), an Islamic eco-cosmological concept formulated in the fourth/tenth century by a Muslim philosopher-scientist group called the Ikhwān al-Ṣafāʾ (fl. third-fourth/ninth-tenth centuries) in their magnum opus, Rasāʾil ("Epistles"). The Ikhwān al-Ṣafāʾ espouse a vision that is spiritually considerate of nature/the universe, based on a more holistic and ontological-metaphysical worldview. The Ikhwān al-Ṣafāʾ recognize the hierarchical structure of existence initiated by God as the origin of all that exists, encompassing both rational-metaphysical entities and physical entities. It is impossible to consider the physical entities in isolation from the metaphysical and the existence of God. In addition to examining the concept of the universe as a great human being, this paper will also investigate certain environmental issues based on the derived entities (al-mawjūdāt al-muwalladāt), including minerals, plants, animals, and humans.